Effect of panretinal photocoagulation on macular morphology and thickness in eyes with proliferative diabetic retinopathy without clinically significant macular edema - Soman M (Dove Medical Press, 2012)
Manoj Soman,1 Sunil Ganekal,2 Unnikrishnan Nair,1 KGR Nair11Chaithanya Eye Hospital and Research Institute, Trivandrum, Kerala, India; 2Nayana Superspecialty Eye Hospital and Research Center, Davangere, Karnataka, IndiaBackground: The purpose of this study was to investigate the effect of panretinal photocoagulation (PRP) on macular morphology and thickness in eyes with proliferative diabetic retinopathy (PDR) and without clinically significant macular edema.Methods: This was a prospective study of 76 eyes from 68 patients diagnosed to have PDR without clinically significant macular edema. Baseline and post PRP visual acuity, morphological changes on optical coherence tomography (OCT), and central foveal thickness were evaluated at one week, one month, and 3 months.Results: The mean patient age was 56.47 ± 6.55 years. Sixty-two eyes (81.58%) had stable or improved vision, while 14 eyes (18.42%) had worsened visual acuity at 3 months. Compared with baseline, mean visual acuity dropped as early as one week but was regained by 3 months. Mean preoperative central foveal thickness was 222.05 ± 59.11 μm, which increased significantly to 266.84 ± 84.67 μm at one week (P = 0.001), and remained higher at 264.05 ± 102.56 μm by one month (P = 0.01) and 256 ± 101.38 μm by 3 months (P = 0.04). Thirty-four percent of eyes with a normal macula showed morphological changes following PRP. The most common morphological change on OCT after PRP was spongy edema, seen in 48 eyes (31.6%), followed by cystoid macular edema in 36 eyes (23.7%), vitreomacular traction in 28 eyes (18.4%), epiretinal membrane in 24 eyes (15.8%), and subfoveal serous detachment in 16 eyes (10.5%).Conclusion: PRP may cause a temporary drop in vision in the early post laser phase, and causes macular morphology/thickness changes in eyes with PDR and without clinically significant macular edema. In this study, the change in central foveal thickness did not correlate with a change in visual acuity, and the type of diabetic macular edema on OCT appeared more relevant and correlated better with the visual outcome.Keywords: panretinal photocoagulation, macular morphology, foveal thickness